Analisis Sustainability Reporting Sebelum dan Sesudah Penerapan Standar Global Reporting Initiative (GRI) 2021 - I Dewa Ayu Eka Pertiwi; Putu Yudha Asteria Putri; I Gusti Ayu Ratih Permata Dewi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze the extent to which changes in the Global Reporting Initiative (GRI) standards can enhance the information disclosed in sustainability reporting. The sampling method employed was purposive sampling, and the data were analyzed using content analysis, with a score assigned to each item. Initially, the study focused on analyzing sustainability reporting from companies in the Oil, Natural Gas, and Coal sectors. However, data collection revealed that in 2021, many companies in these sectors were still adapting to the changes in standards, with only PT Indo Tambangraya Megah Tbk (ITMG), operating in the Coal sector, meeting the research criteria. The results demonstrated an increase in the number of items disclosed in ITMG's Sustainability Reporting prior to and following the implementation of the 2021 GRI Standards. This increase can be attributed to several changes in the requirements for "items that must be disclosed without exception" in the General Disclosure Standard (GRI 2) and the existence of Sector Standards (GRI Standard 12: Coal Sector 2022) as part of the 2021 GRI Standards. These changes also resulted in an increase in information on material topics disclosed by ITMG in sustainability reporting.